Changes of verbal memory in patients with depression during hospitalization - Petraškaitė, Karolina; Jurkuvėnas, Vytautas; Germanavičius, Arūnas; Bagdonas, Albinas (Psichologija, 2015)
Research studies of the cognitive functioning of depressed patients, including different domains of memory, have been inconsistent. Verbal memory dysfunctions partially remain immediately after remission from the depressive state when the course of hospitalization is completed. The aim of this study is to investigate verbal memory changes in patients with depression in the course of hospitalization, taking into account the levels of depression and anxiety. The study involved 30 individuals from the Vilnius Mental Health Centre with a varying severity of single or recruring episodes of depression (6 men and 24 women) receiving antidepressant treatment, with no diagnosed neurological disorders. The study also included 30 healthy individuals matched by age, sex and the level of education. The Hopkins Verbal Learning Test-revised (HVLT-R) and the Hospital Anxiety and Depression Scale (HADS) were used to assess verbal memory, depression and anxiety levels at the beginning and at the end of hospitalization. The study is a quasi-experiment which includes correlations, comparisons of groups, and regression analysis. At the beggining of the hospitalization, the depression group as compared with the control group demonstrated deficits in immediate and delayed recall but not in recognition, and at the end of the treatment the depression group demonstrated deficits only in delayed recall but not in immediate recall or recognition. After the hospitalization course, the results of immediate and delayed recall in the depression group were improved. Worse results are associated with a higher level of depressiveness and anxiety, but only at the end of hospitalization. Further research is required for a more detailed analysis of interaction between cognitive functioning and changes of depression in the course of hospitalization due to the specificity of the depression sample.